Improving throughput in Wireless LAN using Load Balancing Approach - Kunal, Sutar; Mohan, Nikam; Kavita, Gajare; Monali, Khapare; Pooja, Deore (International Journal of Computer Sciences and Engineering, 2014)
In recent years, network bandwidth and quality has been drastically improved in a speed even much faster than the enhancement of computer performance. Various communication and computing tasks in the fields can be integrated and applied in a distributed system in now a days. However, those resources are heterogeneous and dynamic in distributed systems connecting a broad range of resources. This study proposed a hybrid load balancing policy to maintain performance and stability of distributed system. Load balancing is found to reduce significantly the mean and standard deviation of job response times, especially under heavy and/or unbalanced workload. Network overload is one of the key challenges in wireless LANs (WLANs). This goal is classically achieved when the load of access points (APs) is balanced. Recent studies on operational WLAN have shown that AP load is often uneven allocation. To rectify such overload, more than a few load balancing schemes have been proposed. These methods are commonly required proprietary software or hardware at the end side for calculating the user-AP association. In this paper we present a new load balancing method by controlling the size of WLAN cells (i.e., AP’s coverage range), which is conceptually similar to cell breathing in cellular networks. This method does not require any modification to the users neither the wireless standard. It only requires the ability of dynamically changing the transmission power of the AP beacon messages. We build up a set of polynomial time algorithms that locate the optimal beacon power settings which minimize the load of the most congested AP. We also consider the problem of network-wide min-max load balancing.